Pilot evaluation of short-term changes in macular pigment and retinal sensitivity in different phenotypes of early age-related macular degeneration after carotenoid supplementation. Issue 6 (1st September 2016) - Corvi, Federico; Souied, Eric H; Falfoul, Yousra; Georges, Anouk; Jung, Camille; Querques, Lea; Querques, Giuseppe
Abstract : Purpose: To investigate the response of carotenoid supplementation in different phenotypes of early age-related macular degeneration (AMD) by measuring macular pigment optical density (MPOD) and retinal sensitivity. Methods: Consecutive patients with only medium/large drusen and only reticular pseudodrusen (RPD) and age-matched and sex-matched controls were enrolled. At baseline, participants underwent a complete ophthalmological examination including measurement of best-corrected visual acuity (BCVA), MPOD and retinal sensitivity. Patients were put on vitamin supplementation (lutein 10 mg/day, zeaxanthin 2 mg/day) and 3 months later underwent a repeated ophthalmological examination. Results: Twenty patients with medium/large drusen, 19 with RPD and 15 control subjects were included. At baseline, in controls, mean MPOD and BCVA were significantly higher compared with RPD (p=0.001 and p=0.01) but similar to medium/large drusen (p=0.9 and p=0.4). Mean retinal sensitivity was significantly higher in controls compared with RPD and medium/large drusen (for all p<0.0001). After 3 months of carotenoid supplementation the mean MPOD significantly increased in RPD (p=0.002), thus showing no more difference compared with controls (p=0.3); no significant changes were found in mean retinal sensitivity and BCVA (p=0.3 and p=0.7). Medium/large drusen did not show significant changes on MPOD, retinal sensitivity and BCVA (p=0.5, p=0.7 and p=0.7, respectively). Conclusions: Patients with early AMD, especially RPD phenotype, show lower macular sensitivity and MPOD than controls. After supplementation, MPOD significantly increased in RPD. These results suggest different pathophysiology for RPD as compared with medium/large drusen and may open new ways to identifying further therapeutic targets in this phenotype of early AMD.